Age‐related qualitative differences in post‐error cognitive control adjustments. (18th January 2022) - Dubravac, Mirela; Roebers, Claudia M.; Meier, Beat
Abstract: Detecting an error signals the need for increased cognitive control and behavioural adjustments. Considerable development in performance monitoring and cognitive control is evidenced by lower error rates and faster response times in multi‐trial executive function tasks with age. Besides these quantitative changes, we were interested in whether qualitative changes in balancing accuracy and speed contribute to developmental progression during elementary school years. We conducted two studies investigating the temporal and developmental trajectories of post‐error slowing in three prominent cognitive conflict tasks (Stroop, Simon, and flanker). We instructed children (8‐, 10‐, and 12‐year‐old) and adults to respond as fast and as accurately as possible and measured their response times on four trials after correct and incorrect responses to a cognitive conflict. Results revealed that all age groups had longer response times on post‐error versus post‐correct trials, reflecting post‐error slowing. Critically, slowing on the first post‐error trial declined with age, suggesting an age‐related reduction in the orienting response towards errors. This age effect diminished on subsequent trials, suggesting more fine‐tuned cognitive control adjustments with age. Overall, the consistent pattern across tasks suggests an age‐related change from a relatively strong orienting response to more balanced cognitive control adaptations.